2013
DOI: 10.2220/biomedres.34.167
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory effect of catechin-related compounds on renin activity

Abstract: Renin is a crucial enzyme in the renin-angiotensin system, and the inhibition of its activity is considered as a useful approach to the treatment of hypertension. The inhibitory effect of catechinrelated compounds on renin was investigated in this work. It was found that epigallocatechin gallate (EGCg) possessed the strongest activity with an IC 50 value of 44.53 μM and acted in an uncompetitive manner. Gallated catechins exerted higher inhibition than the ungallated forms, and gallic acid exhibited an inhibit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 26 publications
(33 reference statements)
1
23
0
Order By: Relevance
“…12 In addition, some in vitro studies have demonstrated renin-inhibitory activity and vasorelaxation effect by gallic acid. Li et al 13 reported that gallic acid possessed inhibitory activity towards renin, an important enzyme that can cleave the angiotensinogen to yield angiotensin I. This is the rate-limiting step in the production of angiotensin II, a potent vasoconstrictor.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…12 In addition, some in vitro studies have demonstrated renin-inhibitory activity and vasorelaxation effect by gallic acid. Li et al 13 reported that gallic acid possessed inhibitory activity towards renin, an important enzyme that can cleave the angiotensinogen to yield angiotensin I. This is the rate-limiting step in the production of angiotensin II, a potent vasoconstrictor.…”
Section: Resultsmentioning
confidence: 99%
“…Among the identified compounds, gallic acid were previously shown to have some potentials with respect to antihypertensive action. Oral gallic acid was found to significantly reduce blood pressure of diabetic rats 12 and to exhibit renin-inhibitory 13 and vasorelaxation 14,15 effects. However, none has identified the phytochemicals in aqueous decoction of this plant leaf as traditionally prepared.…”
Section: Introductionmentioning
confidence: 96%
“…However, in a recent in vitro study, it has been reported inhibitory properties of EGCG with an inhibitory concentration 50 (IC 50 ) value of 44.53 μM. Furthermore, this study revealed that EGCG acted in an uncompetitive manner and suggested that galloyl moiety and ortho-trihydroxy phenyl structures might be favorable for the renin-inhibitory activity of EGCG [ 138 ]. The beneficial properties of EGCG have been examined on spontaneously hypertensive rats (SHR), a model of hypertension, insulin resistance and obesity.…”
Section: Roles Of Egcg In Hypertensionmentioning
confidence: 99%
“…The renin-angiotensin-aldosterone system (RAAS), which is an important signaling pathway credited with the regulation of extracellular fluid volume, arterial pressure, and tissue perfusion has received significant attention from investigators recently because of its potential as an excellent target for blood pressure lowering agents [3,4,5,6]. Renin and angiotensin I-converting enzyme (ACE) play key roles in the RAAS pathway; renin is responsible for catalyzing hydrolytic production of the inactive decapeptide angiotensin I (AT-I) from the N -terminus of the plasma protein angiotensinogen in what has been recognized as the initial and rate-determining reaction.…”
Section: Introductionmentioning
confidence: 99%